Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1016/j.jsps.2021.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of adverse drug reactions (ADRs) in Saudi Arabia

Abstract: Background Pharmacovigilance enhances post-market drug safety. However, analytical reports of a pattern of adverse drug reactions (ADRs) experienced by patients in Saudi Arabia are demanded. Objective To describe patterns of ADRs submitted to the Saudi Central National Pharmacovigilance and Drug Safety Center (NPC), Saudi Food and Drug Administration (SFDA), from its inception in 2015 until the end of 2017 to understand the pattern of ADR reporting in Saudi Arabia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In KSA, the Saudi Food and Drug Administration (SFDA) established pharmacovigilance activities to oversee the risk–benefit balance of all registered products during their active marketing cycle in in Saudi Arabia. 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In KSA, the Saudi Food and Drug Administration (SFDA) established pharmacovigilance activities to oversee the risk–benefit balance of all registered products during their active marketing cycle in in Saudi Arabia. 22 …”
Section: Discussionmentioning
confidence: 99%
“…In KSA, the Saudi Food and Drug Administration (SFDA) established pharmacovigilance activities to oversee the risk-benefit balance of all registered products during their active marketing cycle in in Saudi Arabia. 22 An earlier study performed on 211 primary healthcare (PHC) physicians in three cities, Dammam, Al-Khobar, and Qatif, revealed that PHC had low knowledge of DFIs. This study suggested that the cause of this low knowledge was that PHC were not adequately trained in DFIs.…”
Section: Discussionmentioning
confidence: 99%
“…The SFDA accepted the spontaneous reporting of post-marketed medications from healthcare professionals, manufacturers, and patients 5 . Meanwhile, the NPC announced and launched several initiatives, including reaching 30,000 ADR reports in 2018 4 ; however, a recent study reported that 17,736 reports were submitted to SFDA in 2017 6 . Furthermore, a previous study revealed that there is still an underreporting of ADRs by HCPs; for example, 10.2% of community pharmacists in Saudi Arabia admitted to submitting an ADR report to NPC 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in 2009 SFDA became a member of the Uppsala Monitoring Centre in Sweden to contribute to global drug safety efforts ( Aljadhey et al, 2015 ). In order to promote and achieve effective national ADR reporting, the Saudi Pharmacovigilance Guidelines relating to Good Pharmacovigilance Practices (GVP) were put forth by the SFDA in 2015, which illustrate the different roles as well as responsibilities of all stakeholders, including the HCPs ( Bin Yousef et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%